The effect of denture cleanser 48% sodium bicarbonate on surface roughness changes of heat-cured acrylic resin - Syahrial ,; Pocut Aya Sofya; Adellya Tasya Sukma (Dentistry Faculty, 2020)
The surface of heat-cured acrylic resin on the base of artificial teeth has a risk of surface roughness. Its causes are liquid absorption and chemical processes. Fluid absorption can be affected by immersion in denture cleaners containing sodium bicarbonate. This study aims to determine the effect of a denture cleanser containing 48% sodium bicarbonate on changes in heat-cured acrylic resin's roughness. This study used 16 specimens of heat-cured acrylic resin (brand Meliodent) and was square in size of 10x10x2.0 0.5 mm. The samples' roughness is measured by using Atomic Force Microscopy (AFM). The specimens were immersed in denture cleansing tablets containing 48% sodium bicarbonate for 17 days at room temperature 25 C and were replaced within 8 hours. After immersion, the specimens were measured again using Atomic Force Microscopy (AFM) to determine the final roughness. The data obtained were analyzed by using paired t-test. The analysis showed no significant difference between surface roughness before and after soaking with a denture cleansing tablet containing 48% sodium bicarbonate (p 0.05). This study concluded that there was no increase in the roughness of heat-cured acrylic resin after immersion in denture cleansing tablets containing 48% sodium bicarbonateKEYWORDS: Fittydent, heat-cured acrylic resin, surface roughness